Speech and voice science - Behrman, Alison; Finan, Donald (Plural Publishing, Inc., 2023)
"Speech and Voice Science, Fourth Edition is the only textbook to provide comprehensive and detailed information on both voice source and vocal tract contributions to speech production. In addition, it is the only textbook to address dialectical and nonnative language differences in vowel and consonant production, bias in perception of speaker identity, and prosody (suprasegmental features) in detail. With the new edition, clinical application is integrated throughout the text"--